Early healing of peri‐implant mucosa in man. (28th July 2016) - Tomasi, Cristiano; Tessarolo, Francesco; Caola, Iole; Piccoli, Federico; Wennström, Jan L.; Nollo, Giandomenico; Berglundh, Tord
Abstract: Aim: To analyse (i) cellular and vascular densities in the connective tissue interface portion of the peri‐implant mucosa and (ii) tissue interactions with the titanium surface during early stages of healing. Materials and Methods: Circumferential biopsies of peri‐implant soft tissues were retrieved together with custom‐made abutments at 27 implants in 21 patients after 2, 4, 6, 8 and 12 weeks of healing. Following fixation, the peri‐implant soft tissue was separated from the abutments, divided into four units and embedded in paraffin. Sections were produced and prepared for immunohistochemical analysis. The abutments were examined by SEM. Results: T and B cells occurred in clusters with a decreasing cell density from 4 to 8 weeks of healing in the connective tissue lateral of the abutment. Macrophages were evenly distributed in the connective tissue along the abutment/tissue interface, while polymorphonuclear (PMN) cells were confined to the tissue portion lateral to the junctional epithelium. Vascular structures showed a decrease in density from 2 to 8 weeks of healing. SEM analyses of the abutments revealed an increased presence of tissue remnants attached to the surface with increasing healing time. A biofilm was consistently observed in a supra‐mucosal position, apical of which a "clear zone" occurred that separated the tissue remnants and the biofilm. Conclusion: Onset and resolution of inflammation together with increasing tissue attachment to the implant characterize healing of peri‐implant mucosa.